Analisis Strategi Pemasaran Produk Frozen Food Untuk Meningkatkan Penjualan Menggunakan Metode Analisis Swot Dan Metode Deksriptif Eksploratif Pada PT Primafood International (Fiesta Group) - Maulani, Farid Rahma (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study conducted a SWOT analysis of PT. Primafood International's marketing strategy to improvemarketing competitiveness, especially in the frozen food sector, where sales and revenue have decreased overthe past year. The method used is a qualitative method with an exploratory descriptive approach, data collectedthrough interviews, direct observation, and secondary and primary sources. The EFE analysis identifiedincreasing market potential (0.6222) as the main opportunity and price wars (0.6984) as the main threat. TheIFE matrix highlights product diversity (0.7718) as the greatest strength and simple management (0.1712) asthe greatest weakness. PT Primafood International is in quadrant II of the IE matrix, indicating the need forgrowth and development. Based on the SWOT analysis, the most appropriate strategy used by the company isto expand cooperation with various agents or resellers in various regions, both in Pasuruan City and PasuruanRegency.